Biocomposites : Biomedical and Environmental Applications - Ahmed, Shakeel, 1989-, editor; Ikram, Saiqa, editor; Kanchi, Suvardhan, editor; Bisetty, Krishna, editor (Singapore : Pan Stanford Publishing, 2018)
Biocomposites, formed by a matrix and a reinforcement of natural fibers, often mimic the structure of living materials and offer the strength of the matrix as well as biocompatibility. Being renewable, cheap, recyclable, and biodegradable, they have witnessed rapidly growing interest in terms of industrial and fundamental applications. This book focuses on fiber-based composites applied to biomedical and environmental applications. It presents a comprehensive survey of biocomposites from the existing literature, paying particular attention to various biomedical and environmental applications. The text describes mechanical designs and manufacturing aspects of various fibrous polymer matrix composites and presents examples of the synthesis and development of bionanocomposites and their applications. The book is the first of its kind to present all these topics together unlike most other books on nano-/biocomposites that are generally limited to their fundamentals, different methods of synthesis, and applications.